2006
DOI: 10.1128/aac.00708-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of P Glycoprotein in Absorption of Novel Antimalarial Drugs

Abstract: Bidirectional transport of four novel antimalarial compounds was determined using Caco-2 cell monolayers. P glycoprotein-mediated efflux was greatest for pyronaridine (5 to 20 M) and low for naphthoquine (5 M). With 20 M naphthoquine, net efflux was blocked, suggesting saturation of the transporter. Piperaquine and dihydroartemisinin were not transported by the system. Permeability glycoprotein (P-gp) ATP-dependent transporters influence the passage of many drugs across epithelial barriers in the intestine, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…This is also seen in clinical use with substantial inter‐individual variability in the pharmacokinetics of piperaquine after oral administration 7, 8. Previously published in vitro findings suggest piperaquine not to be a substrate for P‐glycoprotein and no major efflux by this transporter is therefore to be expected during absorption 15…”
Section: Discussionmentioning
confidence: 93%
“…This is also seen in clinical use with substantial inter‐individual variability in the pharmacokinetics of piperaquine after oral administration 7, 8. Previously published in vitro findings suggest piperaquine not to be a substrate for P‐glycoprotein and no major efflux by this transporter is therefore to be expected during absorption 15…”
Section: Discussionmentioning
confidence: 93%
“…Group 1 patients had additional venous blood samples drawn through the cannula at 1,2,4,8,12,18,24,48, and 72 h and by venesection at 4, 7, 14, 28, 42, and 56 days. Blood was collected into lithium heparin tubes and was centrifuged at 1,800 ϫ g for 5 min, and the separated plasma was stored at Ϫ80°C until analysis for the NQ concentration within 8 months of collection.…”
Section: Methodsmentioning
confidence: 99%
“…These children were reassessed clinically at 4 and 24 h and on days 2, 3, 7, 14, 28, and 56 (7). Group 2 and 3 patients had further 2.5-ml blood samples for drug assay taken at 1,2,4,8,12,18,24,48, and 72 h through the sampling cannula and by venesection at 4, 7, 14, 28, and 42 days. Group 3 patients received a second ART-NQ dose with water at 24 h. Posttreatment clinical and other monitoring for groups 2 and 3 was similar to that performed for group 1 (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive overlap in the substrate specificities, tissue localization, and coinducibility of P-gp and CYP3A4, in which P-gp controls the access of the drug to the metabolizing enzyme and results in increased metabolism from prolonged exposure to the enzyme through repeated cycles of absorption and efflux, has led to the hypothesis that these two proteins work together to protect the body from absorption of harmful xenobiotics, including drugs (1,5,6). It has been reported that some of the antimalarial drugs, like pyronaridine and naphthoquine, are P-gp substrates, which explains their low oral bioavailability (7).…”
mentioning
confidence: 99%